Ranking of districts in Andhra Pradesh using women and children nutrition and health indicators by topsis method - Meshram, Indrapal I; Boiroju, Naveen Kumar; Kodali, Venkaiah (Indian Journal of Community Health, 2017)
Background: Wide variation exists in the nutritional status of under 5 years children among districts/states and more focus is needed on less developed districts in order to allocate resources. Ranking of districts provide baseline information for allocating resources to poor ranking districts and can be considered for comparison of progress in future studies. Aims & Objectives: To rank the districts of Andhra Pradesh state using a multi-criteria decision making method based on the major nutritional and health indicators. Materials and Methods: Data provided by NFHS-4 on nutrition and health indicators of women and children in the state was used to rank the districts in the state. A multi-criteria decision making technique called TOPSIS is used for ranking of the districts in the state based on the selected health indicators. Results: It is observed that Krishna district ranked first and Vizianagaram holds the last rank. The better performing districts include Krishna, Chittoor, East Godavari, Visakhapatnam and Guntur, whereas poor performing districts include Vizianagaram, Kurnool, Srikakulam and Prakasham. Indicators such as per capita income, urbanization, sanitation, use of clean fuel and maternal education were observed high, while infant and maternal mortality was low in in good performing districts. Conclusion: It is concluded that the district with poor nutrition and health indicator ranked last while those with good indicators ranked first. The priority should be given for the development of poor performing districts to improve the above indicators by allocating more resources.